2020
DOI: 10.3390/atmos11030262
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Change of Latent Heat Flux over the Western Tibetan Plateau

Abstract: The Tibetan Plateau (TP) has been experiencing warming and wetting since the 1980s. Under such circumstances, we estimated the summer latent heat flux (LE) using the maximum entropy production model driven by the net radiation, surface temperature, and soil moisture of three reanalysis datasets (ERA5, JRA-55, and MERRA-2) at the Ali site over the western TP during 1980–2018. Compared with the observed LE of the Third Tibetan Plateau Atmospheric Scientific Experiment, the coefficient of determination, root-mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
4
0
2
Order By: Relevance
“…The Tibetan Plateau (TP), with an average elevation exceeding 4000 m, is characterized by complex land surface processes and boundary layer structures (Tao and Ding, 1981;Yanai and Li, 1994;Xu et al, 2002;Yang et al, 2004;Li and Gao, 2007;Sun et al, 2007;Zhou et al, 2018;Zhao et al, 2019a). The ABLH in the TP can reach 2000-3000 m a.g.l., generally higher compared to some plain areas (with ABLH of 1000-1500 m a.g.l.)…”
Section: Introductionmentioning
confidence: 99%
“…The Tibetan Plateau (TP), with an average elevation exceeding 4000 m, is characterized by complex land surface processes and boundary layer structures (Tao and Ding, 1981;Yanai and Li, 1994;Xu et al, 2002;Yang et al, 2004;Li and Gao, 2007;Sun et al, 2007;Zhou et al, 2018;Zhao et al, 2019a). The ABLH in the TP can reach 2000-3000 m a.g.l., generally higher compared to some plain areas (with ABLH of 1000-1500 m a.g.l.)…”
Section: Introductionmentioning
confidence: 99%
“…Thus reducing surface heat flux errors in the WTP is helpful to improve the ABL processes. Some studies have indicated that applying the maximum entropy model in calculating surface heat flux may remarkably reduce surface heat flux errors (Li et al, 2020). Moreover, the coupling error among land evaporation, boundary layer, and convective processes in the reanalysis model would have a significant impact on water vapor and temperature evolutions in the ABL (Betts et al, 1998) and the local atmospheric circulations such as the mountain-valley breezes induced by the combined effects of the complicated TP topography (Yu et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…The lack of the observational data in the TP region has resulted in few efforts to evaluate the quality of the reanalysis datasets. To obtain a long observational data in the western TP, the Third Tibetan Plateau Atmospheric Scientific Experiment (TIPEX-III) has made routine sounding launches at Shiquanhe (SQH), Gaize (GZ), and Shenzha (SZ) stations of the western TP (Figure 1) since 2013, which fills the data gaps in the operational sounding network over the western TP (Zhao et al, 2018;Li et al, 2020). Using the TIPEX-III sounding observational data, Che and Zhao (2021) recently exhibited the west-east differences in the TP ABL height during summer, indicating a deeper ABL in the western TP (up to 4,000 m above ground level) compared to the eastern TP.…”
Section: Introductionmentioning
confidence: 99%
“…La rosa de vientos, para el periodo de medida, Figura 4 (b), da las direcciones y magnitudes predominantes del viento: (i) Este, (ii) Este Nor Este y (iii) Oeste Sur Oeste. La comuna se encuentra distribuida principalmente entre el ángulo subtendido por los puntos cardinales Este -Norte, lo que determinaría una orientación natural de arrastre y dispersión de material particulado por régimen de viento dominante hacia el asentamiento urbano (Córdova et al, 2016;Wang et al, 2020).…”
Section: Localización De Las Medidasunclassified
“…Wang demostró (Wang et al, 2020) que el viento corriente abajo puede promover la propagación de nubes contaminantes, por el contrario, el viento corriente arriba puede suprimir la dispersión a baja intensidad y facilitar la uniformidad de la distribución de la concentración, alineándose con el uso de la rosa de los vientos.…”
Section: Pachecounclassified